Method for detecting tearing strength of film
By applying dynamic tensile force on the dynamic loading device and combining optical measurement systems to measure and calculate the dynamic stress field and crack path energy dissipation of the film sample, the problem of difficulty in evaluating the tear resistance of the film under dynamic conditions is solved, and efficient film tear strength detection is achieved.
Patent Information
- Application Number
- CN202411983068.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-11
AI Technical Summary
The existing film tear strength detection methods are difficult to fully characterize the local mechanical behavior, crack path characteristics and energy dissipation laws at crack tips under dynamic loading conditions.
By preparing a film sample of prefabricated cracks, installing it on a dynamic loading device, dynamic tensile force is applied, and the loading force, crack propagation length and crack tip position are recorded in real time. The dynamic stress field is measured using an optical measurement system, combined with the branch theory of the crack propagation path, the energy dissipation of the crack path is calculated, and the tear strength is calculated based on the film geometric parameters.
The high resolution and high dynamic response detection of the tear strength of the film is achieved, and the tear resistance of the film can be quantitatively evaluated under dynamic conditions, overcoming the shortcomings of the prior art that cannot fully describe crack behavior under dynamic loading conditions.
Smart Images

Figure CN119595467A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mechanical property detection, in particular to a method for detecting the tear strength of a film. Background Art
[0002] Film materials are widely used in packaging, electronic devices, flexible displays, aerospace and other fields due to their light weight, high strength and excellent flexibility. In the actual use of the film, its mechanical properties, especially the tear resistance, are one of the key indicators to measure its reliability and durability. At present, the common tear strength detection method is mainly static testing. For example, the tear test is carried out at a constant tensile rate, the maximum tensile force of the film during crack propagation is measured, and the tear performance is evaluated in combination with the sample geometric parameters. This type of method has been relatively mature in evaluating the basic tear resistance of materials. In addition, some technologies also introduce cracks or cuts of specific shapes to study the expansion behavior of cracks during stress, and use mechanical formulas to calculate the tear strength. These methods have good repeatability and consistency in performance evaluation under static conditions, providing a reliable basis for basic mechanical property testing of film materials.
[0003] However, thin film materials are usually faced with complex and changeable dynamic stress conditions in actual use, such as high-speed stretching, repeated vibration or transient impact. Under such dynamic conditions, crack propagation behavior often shows significant nonlinear characteristics, which places higher requirements on the tear resistance of the material. Existing technologies focus more on the overall mechanical response under static loading conditions, and it is difficult to fully reflect the local stress concentration phenomenon at the crack tip and its evolution law under dynamic conditions. In addition, the existing methods are relatively simple in describing the crack propagation path, and do not fully consider the energy dissipation characteristics of cracks in complex paths such as branching and deflection, which limits the multi-dimensional evaluation of the material's tear resistance. Therefore, in terms of the combination of dynamic loading and crack tip stress field analysis, the existing technology still has room for improvement. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for detecting the tear strength of a film, which solves the technical problem that the existing method for detecting the tear strength of a film is difficult to comprehensively characterize the local mechanical behavior of the crack tip, crack path characteristics and energy dissipation laws under dynamic loading conditions.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for detecting the tear strength of a film, comprising the following steps:
[0006] S1. Prepare a thin film sample. The size of the thin film sample is rectangular. A straight crack with a length equal to the initial crack is prefabricated in the center. The crack tip is smooth and aligned with the loading direction.
[0007] S2, install the film sample on the dynamic loading device, apply dynamic tensile force through the servo loading system, and record the loading force, crack extension length and crack tip position in real time;
[0008] S3, measuring the dynamic stress field at the crack tip of the film sample by an optical measurement system, extracting the stress intensity factor at the crack tip, and calculating the dynamic stress intensity at the crack tip in combination with the loading rate and the crack extension rate;
[0009] S4. Based on the dynamic stress field at the crack tip and the crack propagation path branching theory, the angle change of the crack propagation path is measured and the energy dissipation of the crack path is calculated;
[0010] S5. Calculate the tear strength of the film based on the crack tip stress field and path energy dissipation data.
[0011] Preferably, in step S1, the crack tip width is ≤0.1 mm, the crack direction is strictly aligned with the loading direction, and the sample thickness deviation is controlled within ±0.01 mm.
[0012] Preferably, in step S2, the loading rate of the dynamic loading device is adjustable in the range of 0.1 m / s to 10 m / s, and the loading force is recorded in real time by a high-precision sensor with an accuracy of ±0.1 N.
[0013] Preferably, in step S3, the optical measurement system includes a digital image correlation measurement device and a high-speed camera, the digital image correlation device is used to measure the strain field and displacement field at the crack tip, the sampling frame rate of the high-speed camera is ≥1000fps, the random speckle size of the optical resolution is 30μm to 50μm, and the displacement measurement accuracy is ≤10μm / pixel.
[0014] Preferably, in step S3, the dynamic stress intensity factor is calculated by the ratio of the loading force to the square root of the crack length, combined with a speed correction factor of the loading rate, which is related to the ratio of the crack growth rate to the Rayleigh wave velocity of the material.
[0015] Preferably, in step S4, the branching angle of the crack propagation path is calculated by the minimum energy dissipation principle, and the energy dissipation of the crack propagation path is proportional to the square of the stress intensity at the crack tip and the material characteristic factor.
[0016] Preferably, in step S4, the dynamic stress field at the crack tip is described by a polar coordinate expression, and the stress distribution at the crack tip is inversely proportional to the square root of the distance from the crack tip to the measuring point, and is multiplied by a distribution function related to the crack propagation speed and angle.
[0017] Preferably, in step S4, the crack growth rate is calculated by collecting the change of the crack tip position over time through an optical measurement system, and the crack growth rate is used to correct the dynamic stress intensity factor of the crack tip.
[0018] Preferably, in step S5, the tear strength of the film is calculated by integrating the dynamic stress intensity factor at the crack tip and the energy dissipation of the crack path, and the tear strength is proportional to the inverse of the film thickness.
[0019] Preferably, in step S5, by repeatedly measuring the dynamic stress field at the crack tip and the crack propagation path of the same material sample, the tear strength results are fitted and the consistency is verified to ensure the reliability and repeatability of the data.
[0020] The present invention provides a method for detecting the tear strength of a film, which has the following beneficial effects:
[0021] 1. The present invention realizes the accurate description of the local stress field at the crack tip by real-time recording of loading force, crack propagation speed and dynamic stress intensity factor, and achieves the technical effect of high resolution and high dynamic response. Compared with the technical solution of the prior art that only relies on static tearing force for strength assessment, it solves the deficiency that it cannot characterize the local mechanical behavior of the crack under dynamic loading conditions.
[0022] 2. The present invention proposes an energy consumption-driven path optimization method by combining the branch angle analysis of the crack propagation path and the minimum energy dissipation model, thereby achieving the technical effect of quantitatively analyzing the crack propagation path and directional behavior. Compared with the detection scheme in the prior art that only focuses on the crack propagation length and ignores the path complexity, it solves the technical problem that the crack propagation behavior is difficult to describe under nonlinear and branching paths.
[0023] 3. The present invention adopts a synchronous integration method of dynamic loading and optical measurement system, and obtains the displacement field and strain field of the crack tip in real time through digital image correlation technology and a high-speed camera, thereby achieving the technical effect of high-precision synchronization of dynamic test data and loading process. Compared with the technical solutions of manual recording or low-frequency measurement in the prior art, it overcomes the problems of inconsistent test data timing and insufficient capture of key crack behaviors.
[0024] 4. The present invention establishes a mathematical model of tear strength, combines the dynamic stress intensity factor, the energy dissipation of the crack path and the geometric parameters of the film, and proposes a comprehensive and quantifiable tear strength calculation method, which achieves the technical effect of quantifying and accurately evaluating the tear resistance of the film. Compared with the calculation method based on empirical formulas or local test data in the prior art, it solves the deficiency that the prior art is difficult to cover the influence of multiple factors under dynamic crack propagation conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a flow chart of the method steps of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Please see attached Figure 1 The present invention provides a method for detecting the tear strength of a film, comprising the following steps:
[0028] S1. Prepare a thin film sample. The size of the thin film sample is rectangular. A straight crack with a length equal to the initial crack is prefabricated in the center. The crack tip is smooth and aligned with the loading direction.
[0029] S2, install the film sample on the dynamic loading device, apply dynamic tensile force through the servo loading system, and record the loading force, crack extension length and crack tip position in real time;
[0030] S3, measuring the dynamic stress field at the crack tip of the film sample by an optical measurement system, extracting the stress intensity factor at the crack tip, and calculating the dynamic stress intensity at the crack tip in combination with the loading rate and the crack extension rate;
[0031] S4. Based on the dynamic stress field at the crack tip and the crack propagation path branching theory, the angle change of the crack propagation path is measured and the energy dissipation of the crack path is calculated;
[0032] S5. Calculate the tear strength of the film based on the crack tip stress field and path energy dissipation data;
[0033] In step S1, the crack tip width is ≤0.1 mm, the crack direction is strictly aligned with the loading direction, and the sample thickness deviation is controlled within ±0.01 mm;
[0034] In step S2, the loading rate of the dynamic loading device is adjustable in the range of 0.1m / s to 10m / s, and the loading force is recorded in real time by a high-precision sensor with an accuracy of ±0.1N;
[0035] In step S3, the optical measurement system includes a digital image correlation measurement device and a high-speed camera. The digital image correlation device is used to measure the strain field and displacement field at the crack tip. The sampling frame rate of the high-speed camera is ≥1000fps, the random speckle size of the optical resolution is 30μm to 50μm, and the displacement measurement accuracy is ≤10μm / pixel.
[0036] In step S3, the dynamic stress intensity factor is calculated by the ratio of the loading force to the square root of the crack length, combined with a velocity correction factor of the loading rate, which is related to the ratio of the crack growth rate to the material Rayleigh wave velocity;
[0037] In step S4, the branching angle of the crack propagation path is calculated by the principle of minimum energy dissipation. The energy dissipation of the crack propagation path is proportional to the square of the stress intensity at the crack tip and the material characteristic factor.
[0038] In step S4, the dynamic stress field at the crack tip is described by a polar coordinate expression. The stress distribution at the crack tip is inversely proportional to the square root of the distance from the crack tip to the measurement point and is multiplied by the distribution function related to the crack growth rate and angle.
[0039] In step S4, the crack growth rate is calculated by collecting the change of the crack tip position over time through the optical measurement system, and the crack growth rate is used to correct the dynamic stress intensity factor of the crack tip;
[0040] In step S5, the tear strength of the film is calculated by integrating the dynamic stress intensity factor at the crack tip and the energy dissipation of the crack path, and the tear strength is proportional to the inverse of the film thickness;
[0041] In step S5, the dynamic stress field at the crack tip and the crack propagation path of the same material sample are repeatedly measured to fit and verify the consistency of the tear strength results to ensure the reliability and repeatability of the data.
[0042] Specifically, step S1 involves the preparation of film samples. This is the basis and starting point of the entire testing process. The quality of sample preparation is directly related to the accuracy and reliability of subsequent tests. In order to ensure the repeatability of the test and the scientific nature of the data, this step strictly regulates the size of the film sample, the accuracy of crack prefabrication, and the surface treatment.
[0043] Generally, the film samples are prepared in a rectangular shape, and the size is usually selected as 100mm×63mm. Samples within this size range are easy to fix and clamp, and are not prone to edge fracture or premature failure during loading. In some embodiments, the sample thickness t can be selected in the range of 0.01mm to 0.2mm, but the thickness deviation must be strictly controlled within ±0.01mm to avoid stress concentration caused by uneven thickness.
[0044] Specifically, the crack is prefabricated using a high-precision laser cutting machine. The crack shape is a linear crack with an initial length a0 of 10 mm. The crack direction needs to be strictly parallel to the loading direction to avoid path deviation problems caused by non-uniform stretching. As an option, the width of the crack tip should be less than or equal to 0.1 mm to ensure that the crack tip has ideal smoothness and concentration. The crack tip surface should avoid defects caused by machining, such as burrs or microcracks, which have an important influence on the mechanical properties of the starting point of crack propagation.
[0045] In some possible implementations, in order to better carry out optical measurements and subsequent data analysis, a random speckle pattern is uniformly sprayed on the surface of the thin film sample. The size of the sprayed random speckle should be controlled in the range of 30μm to 50μm. The high-contrast coating of the speckle pattern not only facilitates the full-field measurement of the digital image correlation (DIC) technology, but also improves the accuracy of the displacement field and strain field data acquisition at the crack tip. In general, the coating process requires the use of a spraying device to evenly distribute the coating to avoid local fluctuations in the speckle density.
[0046] As a better option, the adhesion of the speckle coating can be further enhanced by UV curing technology after spraying the speckle. This can effectively prevent the coating from falling off due to the stretching of the film during loading, ensuring the consistency and continuity of the full-field measurement.
[0047] In order to reduce the impact of edge tearing or defects, the edges of the sample can be trimmed and polished to make the edges have a smooth arc transition. Such a design can reduce the stress concentration at the edge and concentrate the main stress in the crack tip area during loading.
[0048] In addition, the environmental conditions of the samples also need to be strictly controlled. Specifically, the samples should be stored in the laboratory environment for at least 24 hours before testing to ensure that the effects of temperature and humidity on the performance of the film material are minimized. The laboratory temperature is recommended to be controlled at 25°C and the humidity is controlled at 50%, which is particularly important in the performance stability research of some special materials (such as polymer films or composite films).
[0049] According to the theory of dynamic fracture mechanics, the geometric shape of the crack tip directly determines the stress distribution characteristics of the crack tip, especially the calculation of the intensity factor in the dynamic stress field. A crack tip width that is too large may weaken the stress concentration phenomenon, while a misaligned crack direction may induce an asymmetric stress field. These undesirable phenomena will cause the dynamic stress intensity factor K d The measured value of (v) deviates from the true value, thus affecting the final tear strength calculation result.
[0050] The dynamic stress field at the crack tip is usually described mathematically as follows:
[0051]
[0052] in:
[0053] σ ij (r, θ, v): stress components at the crack tip;
[0054] K d (v): dynamic stress intensity factor at the crack tip;
[0055] r: distance from crack tip to measuring point;
[0056] θ: The angle of the measuring point relative to the crack tip, in radians;
[0057] f ij (θ, v): stress distribution function at the crack tip, which is related to the angle and the propagation velocity.
[0058] Step S2 is the process of dynamically loading the sample and collecting relevant data in real time. This step directly inherits the standardized sample prepared in step S1, applies dynamic tensile force through the servo loading system, and records the crack propagation behavior in combination with a high-precision measuring device. This step is the basis for subsequent dynamic stress field analysis and tear strength calculation.
[0059] In general, the loading rate of thin film samples is designed to be adjustable in the range of 0.1m / s to 10m / s. This range can cover the stress loading requirements of most actual working conditions, such as static stretching at low speed and high-speed dynamic impact. The loading force is recorded in real time by a high-precision sensor, and the accuracy of the force sensor is set to ±0.1N. Specifically, the dynamic loading device ensures the stability of the loading rate through a servo control system to avoid fluctuations in stress intensity at the crack tip caused by rate fluctuations.
[0060] In some embodiments, in order to ensure the synchronous recording of the loading force and the crack propagation behavior, a unified time trigger signal is used between the loading device and the optical measurement system. The sampling frequency of the loading data and the optical measurement data is set to 10kHz, which can fully capture the subtle changes in the dynamic loading process.
[0061] The fixture needs to be rigid enough to prevent deformation during loading. The clamping surface of the fixture is made of high friction material to ensure that the film sample is firmly fixed without slipping. In some implementations, the fixture can be designed with adjustable size to accommodate film samples of different widths and thicknesses.
[0062] Generally, the contact surface between the clamp and the sample should avoid excessive edge stress concentration. Therefore, in some embodiments, the edges of the clamp are rounded and the clamping pressure is evenly distributed. These details can significantly reduce additional crack propagation or tear path deviation caused by clamping problems during loading.
[0063] Specifically, the loading process in this embodiment requires real-time recording of the relationship between the loading force and the displacement of the crack extension, and the relationship curve between the loading force and time is the core data for the subsequent calculation of the dynamic stress intensity factor.
[0064] The relationship between the loading force and the crack extension length a(t)a(t)a(t)usually satisfies the following formula:
[0065]
[0066] in:
[0067] F represents the loading force;
[0068] a is the total length of the crack;
[0069] Φ(v) is the velocity correction factor, which is related to the crack growth velocity v and the material Rayleigh wave velocity c. R The ratio is related.
[0070] As a possible implementation method, the measurement of the crack growth velocity v is to record the change of the crack tip position over time through an optical system. The formula is as follows:
[0071]
[0072] in:
[0073] x is the position of the crack tip;
[0074] t is time.
[0075] In a possible implementation, in order to improve the stability of the loading process and the data quality, the loading system may also be equipped with a dynamic compensation mechanism.
[0076] For example, when the rate fluctuates or the force value deviates from the preset value during loading, the servo system's feedback control function automatically adjusts the loading parameters to keep the force value and rate stable. This dynamic compensation mechanism is particularly suitable for thin film material testing under high-speed loading conditions and can effectively reduce system errors.
[0077] In addition, in some extended embodiments, environmental variables (such as temperature and humidity) during the loading process also need to be strictly controlled. The recommended temperature of the experimental environment is 25°C and the humidity is 50%. Under this condition, the performance of the film material is relatively stable, which can minimize the influence of the external environment on the crack propagation behavior;
[0078] The main task of step S3 is to measure the dynamic stress field at the crack tip. This process is achieved through an optical measurement system, including the stress distribution at the crack tip, the extraction of the dynamic stress intensity factor, and the calculation of the crack propagation rate. Step S3 directly receives the data of dynamic loading in S2, and provides key input for subsequent crack path and tear strength calculations through high-precision measurement and data processing;
[0079] Generally, the optical measurement system includes a digital image correlation device (DIC) and a high-speed camera. The frame rate of the high-speed camera is set to 1000fps or higher, which can capture the microscopic changes of the crack tip during dynamic loading. Specifically, the spatial resolution of the camera is set to 10μm, which can clearly record the details of the local area of the crack tip.
[0080] In some embodiments, in order to improve the data accuracy of the crack tip area, the distribution density of the speckle coating is strictly controlled, and the diameter of the speckle ranges from 30μm to 50μm. This design ensures the image contrast near the crack tip while avoiding measurement errors caused by speckle overlap.
[0081] Specifically, the DIC system uses the captured speckle image to calculate the displacement field and strain field distribution at the crack tip through a pixel matching algorithm. The local displacement data of the crack tip area is the core input for the subsequent stress intensity factor calculation.
[0082] In general, the stress distribution at the crack tip follows the following mathematical relationship:
[0083]
[0084] in:
[0085] σ ij (r, θ, v) represents the stress component at the crack tip;
[0086] r is the distance from the crack tip to the measuring point;
[0087] θ is the angle of the measuring point relative to the crack tip;
[0088] v is the crack growth rate;
[0089] K d (v) is the dynamic stress intensity factor;
[0090] f ij (θ, v) is the stress distribution function related to angle and velocity.
[0091] This formula states that the stress intensity at the crack tip is inversely proportional to the square root of the distance r and is multiplied by the distribution function related to the angle and crack growth rate. Dynamic Stress Intensity Factor K d (v) is a characterization of the concentration of local stress at the crack tip, and its magnitude directly determines the crack propagation behavior.
[0092] In some embodiments, the extraction of dynamic stress intensity factors relies on real-time data of the loading force and propagation length at the crack tip.
[0093] Dynamic stress intensity factor K d The calculation formula for (v) is:
[0094]
[0095] in:
[0096] F is the dynamic loading force;
[0097] a is the total length of the crack;
[0098] Φ(v) is the velocity correction factor, whose value is determined by the crack growth velocity v and the material Rayleigh wave velocity c R Calculate the ratio of:
[0099]
[0100] In general, the crack growth velocity v is calculated by monitoring the position of the crack tip over time. Specifically, the velocity expression is:
[0101]
[0102] in:
[0103] x is the position of the crack tip;
[0104] t is time.
[0105] In order to further improve the reliability of the measurement data, some embodiments include an environmental compensation mechanism and a data processing algorithm.
[0106] For example, when the test environment temperature fluctuates greatly, a temperature sensor can be used to record the environmental data in real time and introduce it as a parameter into the stress field calculation. When the crack tip propagation speed is extremely high, the image data can be interpolated to compensate for the time interval deviation caused by insufficient image frame rate.
[0107] Specifically, the data processing algorithm can also filter the measured data to eliminate noise interference. The filtering method can be Gaussian filtering or wavelet transform-based filtering, which can effectively retain the dynamic characteristics of the crack tip area while suppressing measurement errors.
[0108] Step S4 is a process of measuring the crack propagation path and analyzing the angle change and energy dissipation behavior of crack propagation based on the dynamic stress field data at the crack tip. This step is closely related to step S3, relying on the measurement data of the dynamic stress field, and providing quantitative results of the crack path and branching behavior for the final calculation of the tear strength.
[0109] In general, the crack propagation path is not strictly linear. The dynamic stress field distribution at the crack tip will form a complex mechanical balance inside the material, causing the crack propagation direction to deflect or branch. Specifically, the crack path branching angle is determined by the stress intensity factor K at the crack tip. d (v) and the internal structure of the material. The crack propagation angle θ(t) recorded by the optical measurement system is the basis for subsequent calculations.
[0110] In some embodiments, the energy dissipation of the crack propagation path is calculated by integrating the stress distribution on the path. To ensure the accuracy of the path analysis, the position and direction of each point on the path must be recorded synchronously with time. These data provide conditions for quantifying crack branching behavior and energy dissipation.
[0111] As a possible implementation, the branching angles of the crack paths are calculated using the principle of minimum energy dissipation.
[0112] Generally speaking, the branching or deflection of the crack path follows the following principle: the crack propagates in the direction with the least energy dissipation, and its branching angle θ c The calculation formula is:
[0113] θ c =argminΓ(θ)
[0114] in:
[0115] Γ(θ) represents the energy dissipation of the path.
[0116] The energy dissipation of the path Γ(θ) is determined by the dynamic stress intensity factor and the material property correction factor, and its expression is:
[0117]
[0118] in:
[0119] K d (v) is the dynamic stress intensity factor at the crack tip;
[0120] g(θ) is the path direction correction factor, which is a dimensionless quantity that characterizes the relationship between the internal structure of the material and the crack propagation direction.
[0121] In general, the correction factor g(θ) can be obtained by experimentally calibrating the anisotropic parameters of the material, or it can be combined with theoretical models to analyze the impact of the local heterogeneity of the material on the crack path.
[0122] In this embodiment, in order to further improve the calculation accuracy of the path branching angle, the dynamic stress field data at the crack tip and the crack extension path data need to be subjected to multi-level analysis and processing.
[0123] As a possible implementation method, the calculation of the path branch angle combines the displacement field data of the optical measurement system and the analytical results of the dynamic stress field. The expression of the dynamic stress field in polar coordinates is:
[0124]
[0125] in:
[0126] σ ij (r, θ, v) is the stress component at the crack tip;
[0127] f ij (θ, v) is the distribution function related to angle and expansion speed;
[0128] r is the distance from the crack tip to the measuring point.
[0129] Specifically, in this embodiment, the optical measurement of crack path branches relies on high frame rate recording by a high-speed camera.
[0130] During the experiment, the angle change θ(t) of the crack tip extension is captured frame by frame, and its dynamic change curve over time is recorded. These data are calculated using the digital image correlation (DIC) algorithm to obtain the actual extension direction of the crack path. In general, the deflection angle of the crack path is more obvious under high-speed dynamic loading, so the resolution of the optical measurement system must meet the requirements of capturing path details.
[0131] In some embodiments, in order to improve the reliability of path data, a multi-path analysis model can also be introduced. By comparing and analyzing the crack propagation paths under multiple loading conditions, the statistical laws of crack branching angles can be extracted. This method can eliminate the interference of random factors in a single experiment and obtain a more universal path branching model.
[0132] As an option, in this embodiment, the energy dissipation of the crack path can also be combined with local material performance parameters for correction analysis.
[0133] For example, for multilayer composite films, the crack path may change suddenly between layers. In this case, the correction factor needs to be redefined in combination with the strength parameters of the layered interface. In the testing of some high-performance film materials (such as nano-enhanced films), the microscopic bending effect of the crack path also needs to be considered. These additional analyses can obtain supplementary data through micromechanical simulation or experimental verification.
[0134] Step S5 is the final tear strength calculation process. Based on the dynamic stress field data at the crack tip obtained in the previous steps and the energy dissipation analysis of the crack propagation path, combined with geometric parameters such as the thickness of the film material, the tear strength value of the film is calculated. This step is a summary of the entire detection process and provides quantitative results for the performance evaluation of different film materials.
[0135] In this embodiment, the calculation core of the tear strength is to integrate the analysis results of the dynamic stress intensity factor and the crack path energy dissipation, and establish a mathematical relationship between them and the geometric properties of the film.
[0136] In general, the tear strength T is defined as the maximum energy dissipation required for a unit thickness of the film during crack propagation. Its calculation formula is:
[0137]
[0138] in:
[0139] T is the tear strength of the film;
[0140] t is the film thickness;
[0141] a c is the critical length of crack extension;
[0142] K d (v) is the dynamic stress intensity factor;
[0143] Γ(θ) is the energy dissipated along the crack path.
[0144] Generally speaking, the energy dissipation Γ(θ) of the crack path can be directly derived from the data obtained in the aforementioned step S4.
[0145] In a possible implementation, the calculation of tear strength requires numerical integration of the time series data of the dynamic stress field at the crack tip.
[0146] Total crack length a c Including the initial crack length and the extended crack length. The change of the extended crack length is recorded in real time by the optical measurement system, and its calculation formula is:
[0147]
[0148] in:
[0149] v(t) is the crack growth rate;
[0150] t c The time required for the crack to grow to the critical length.
[0151] Through this formula, the total crack extension length a can be obtained c , thus providing specific data for the integral boundary in the tear strength calculation.
[0152] In this embodiment, in order to improve the calculation accuracy of the tear strength, the dynamic stress intensity factor K can be d (v) is fitted nonlinearly with the crack growth velocity v.
[0153] In general, the dynamic stress intensity factor K d (v) is a function of the crack growth rate, and its specific form can be obtained through experimental calibration or theoretical modeling. In some embodiments, it can be assumed that K d (v) It changes exponentially with the crack growth rate, and its fitting relationship is:
[0154] K d (v) = K0·e -αv
[0155] in:
[0156] K0 is the stress intensity factor under static conditions;
[0157] α is the velocity correction coefficient, which represents the attenuation effect of crack growth rate on the stress intensity factor.
[0158] This fitting method can reduce the calculation error caused by data fluctuation under dynamic loading conditions and make the tear strength results more stable and reliable.
[0159] Specifically, in this embodiment, the calculation of tear strength also needs to be combined with the measurement results of film thickness. As an option, the film thickness can be measured by a microscope or a laser thickness gauge, and its accuracy is usually ±0.01mm. The change of film thickness has a direct impact on the tear strength, especially in the test of multi-layer composite films, the thickness distribution of each layer will significantly change the energy dissipation characteristics of the crack path.
[0160] In some embodiments, in order to eliminate the influence of local fluctuations in film thickness on the calculation results, the thickness data of different parts of the sample can be averaged. This method can further improve the reliability of tear strength calculation.
[0161] Generally speaking, multiple experimental data of the same material should have good consistency. However, under high dynamic loading conditions, the randomness of the crack propagation path may cause certain deviations in the data. To solve this problem, statistical methods can be used to process the tear strength calculation results. For example, the distribution characteristics of the tear strength can be obtained through multiple experiments, and then the average value is taken as the final result.
[0162] In addition, the error analysis method can be combined to separate and quantify the systematic and random errors in the experimental data. This process can be completed by analyzing the time series of the loading force and crack extension length data.
[0163] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for detecting film tear strength, characterized in that: The following steps are involved: S1. Prepare a thin film sample. The size of the thin film sample is rectangular. A straight crack with a length equal to the initial crack is prefabricated in the center. The crack tip is smooth and aligned with the loading direction. S2, install the film sample on the dynamic loading device, apply dynamic tensile force through the servo loading system, and record the loading force, crack extension length and crack tip position in real time; S3, measuring the dynamic stress field at the crack tip of the film sample by an optical measurement system, extracting the stress intensity factor at the crack tip, and calculating the dynamic stress intensity at the crack tip in combination with the loading rate and the crack extension rate; S4. Based on the dynamic stress field at the crack tip and the crack propagation path branching theory, the angle change of the crack propagation path is measured and the energy dissipation of the crack path is calculated; S5. Calculate the tear strength of the film based on the crack tip stress field and path energy dissipation data.
2. A method for detecting film tear strength according to claim 1, characterized in that: In the step S1, the crack tip width is ≤0.1 mm, the crack direction is strictly aligned with the loading direction, and the sample thickness deviation is controlled within ±0.01 mm.
3. A method for detecting film tear strength according to claim 1, characterized in that: In the step S2, the loading rate of the dynamic loading device can be adjusted in the range of 0.1 m / s to 10 m / s, and the loading force is recorded in real time by a high-precision sensor with an accuracy of ±0.1 N.
4. A method for detecting film tear strength according to claim 1, characterized in that: In the step S3, the optical measurement system includes a digital image correlation measurement device and a high-speed camera. The digital image correlation device is used to measure the strain field and displacement field at the crack tip. The sampling frame rate of the high-speed camera is ≥1000fps, the random speckle size of the optical resolution is 30μm to 50μm, and the displacement measurement accuracy is ≤10μm / pixel.
5. A method for detecting film tear strength according to claim 1, characterized in that: In the step S3, the dynamic stress intensity factor is calculated by the ratio of the loading force to the square root of the crack length, and is combined with a speed correction factor of the loading rate, which is related to the ratio of the crack growth rate to the Rayleigh wave velocity of the material.
6. A method for detecting film tear strength according to claim 1, characterized in that: In the step S4, the branching angle of the crack propagation path is calculated by the minimum energy dissipation principle, and the energy dissipation of the crack propagation path is proportional to the square of the stress intensity at the crack tip and the material characteristic factor.
7. A method for detecting film tear strength according to claim 1, characterized in that: In step S4, the dynamic stress field at the crack tip is described by a polar coordinate expression, and the stress distribution at the crack tip is inversely proportional to the square root of the distance from the crack tip to the measuring point, and is multiplied by a distribution function related to the crack propagation speed and angle.
8. A method for detecting film tear strength according to claim 1, characterized in that: In the step S4, the crack growth rate is calculated by collecting the change of the crack tip position over time through the optical measurement system, and the crack growth rate is used to correct the dynamic stress intensity factor of the crack tip.
9. A method for detecting film tear strength according to claim 1, characterized in that: In the step S5, the tear strength of the film is calculated by integrating the dynamic stress intensity factor at the crack tip and the energy dissipation of the crack path, and the tear strength is proportional to the inverse of the film thickness.
10. A method for detecting film tear strength according to claim 1, characterized in that: In the step S5, the dynamic stress field at the crack tip and the crack propagation path of the same material sample are repeatedly measured to fit and verify the consistency of the tear strength results, thereby ensuring the reliability and repeatability of the data.
Citation Information
Cited By
Method and system for testing bonding strength of laser cladding layer
CN120467915A